Diffuse reduction of cerebral grey matter volumes in Erdheim-Chester disease. Issue 1 (December 2016) - Diamond, Eli; Hatzoglou, Vaios; Patel, Sneha; Abdel-Wahab, Omar; Rampal, Raajit; Hyman, David; Holodny, Andrei; Raj, Ashish
Abstract Background Erdheim-Chester disease (ECD) is a rare non-Langerhans histiocytosis characterized by systemic inflammation and granulomatous infiltration of multiple organs including the central nervous system (CNS), bones, and retroperitoneum. CNS infiltration occurs in one third of patients, but cognitive changes are common in patients without CNS disease. Here we investigate whether there is a neuroanatomic basis to observed cognitive deficits, even in absence of CNS disease. Methods We present a volumetric analysis of eleven ECD patients without CNS tumors or prior neurotoxic treatments. Results Compared to age-matched controls, ECD patients have diffuse, bihemispheric reduction in cortical thickness and subcortical gray matter. Conclusions These findings provide the first corroborating evidence for neurologic disease in ECD patients without direct CNS infiltration.